(untitled) (Isagoge - Journal of Humanities and Social Sciences, 2025)
This article explores the evolving role of fathers in early childhood development through a child rights lens. Anchored in the United Nations Convention on the Rights of the Child (CRC)—particularly Articles 5, 18, and 27, which stress the best interests of the child—it challenges the enduring stereotype of fathers as solely financial providers. Employing a normative-analytical approach, the paper critically reviews international legal frameworks and scholarly literature to identify socio-cultural and institutional barriers to paternal involvement, especially within the Global South. Focusing on Indonesia—due to its recent legal reforms and entrenched gender norms—the study proposes a reconceptualisation of fatherhood across four key dimensions: emotional presence, hands-on caregiving, respectful dialogue, and cooperative co-parenting. It presents a set of evidence-informed policy and practice recommendations that position fathers as active, equal partners in nurturing and protecting young children. By offering a rights-based normative framework, this study contributes to global discourse on gender-transformative parenting and affirms every child’s right to balanced, nurturing care from both parents. This conceptual contribution connects legal, cultural, and policy domains, advancing a vision of fatherhood grounded in justice, equity, and the principles of the CRC.